Spinal Astrocytes as Therapeutic Targets for Pathological Pain - Takayuki Nakagawa; Shuji Kaneko (Elsevier, 2010)
Abstract.: Development of next-generation analgesics requires a better understanding of the molecular and cellular mechanisms underlying pathological pain. Accumulating evidence suggests that the activation of glia contributes to the central sensitization of pain signaling in the spinal cord. The role of microglia in pathological pain has been well documented, while that of astrocytes still remains unclear. After peripheral nerve inflammation or injury, spinal microglia are initially activated and subsequently sustained activation of astrocytes is precipitated, which are implicated in the induction and maintenance of pathological pain. Astrocytic activation is caused by the production of diffusible factors from primary afferent neurons (neuron-to-astrocyte signals) and activated microglia (microglia-to-astrocyte signals). Although astrocyte-to-neuron signals implicated in pathological pain is poorly understood, activated astrocytes, as well as microglia, produce proinflammatory cytokines and chemokines, which lead to adaptation of the dorsal horn neurons. Furthermore, it has been suggested that glial glutamate transporters in the spinal astrocytes are down-regulated in pathological pain and that up-regulation or functional enhancement of these transporters prevents pathological pain. This review will briefly discuss novel findings on the role of spinal astrocytes in pathological pain and their potential as a therapeutic target for novel analgesics. Keywords:: astrocyte, glutamate transporter, neuron-glial network, pain, spinal cord